(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This paper examines the functional capabilities of CorelDRAW and Photoshop, their role in graphic design, and the specifics of their integration. The study focuses on the combination of vector and raster graphics, workflow optimization, color management, and file exchange. The findings highlight the importance of a comprehensive digital design approach.